The Translation of Idioms in Rowling’s "Harry Potter and the Prisoner of Azkaban" into Indonesian - Mustika Pratiwi Putri N. (Lexicon, 2012)
This study analyzes the idioms and its translation strategies used in novel Harry Potter and the Prisoner of Azkaban. RThe rsearcher classifies the translation strategies by using accuracy analysis. The result of this research shows that there are three strategies used by the Indonesian translator. The first strategy is idiom to idiom, which means transferring idioms in English into idioms in Indonesian. This method is used when two idioms, in both English and Indonesian, contain the same form and meaning. Second method is paraphrase, which means transferring idioms in English directly into its real meaning in Indonesian. This strategy is the most frequently used considering the fact that it is very difficult to find idioms in Indonesian that has the same meaning and form with the idioms in English. The third method is literal translation. In some cases, idioms in English can be literally translated. This kind of case is specifically occurs when an idiom happens to be part of a dialogue or informal sentence.